Psikologi Kriminal terhadap Malpraktik Hipnoterapis dalam Kasus Percabulan Anak Ditinjau dari Perspektif Penegakan Hukum - Lucy Lidiawati Santioso; Marjan Miharja; Dadang Herli (Syntax Literate, 2023)
The purpose of this study is to examine criminal psychology towards hypnotherapist malpractice in child fornication cases from a law enforcement perspective. The research method used in this study is normative juridical, namely research focused on examining rules or norms in positive law, using Secondary Data (official documents, books, research results in the form of reports, journals and so on). And the results of this study the author examines that there is a weak mental attitude and conscience of the defendant so that his ego seeks satisfaction and is difficult to control the impulses of an insatiable sexual instinct, in accordance with the theory of psychoanalysis, Sigmund Freud.